KOMUNIKASI POLITIK CALON WALIKOTA PETAHANA DR.H.FIRDAUS,ST,MT DALAM KAMPANYE PEMILIHAN KEPALA DAERAH WALIKOTA PEKANBARU 2017-2022 - Dwi Elsa Wahyuni; Belli Nasution (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
2017 is the year of political party head again in the city of Pekanbaru precisely the turn of the term of mayor and vice mayor of Pekanbaru and the election of Pekanbaru mayor. The election of the head of this region was followed by the incumbent mayoral candidate and incumbent mayor’s deputy. At wednesday, February 15, 2017 election of the head of Pekanbaru city was held. The incumbent partner outperformed the other partner with the most voting 33,16% and was declared to win regional head election which made this pair again become mayor and deputy mayor of Pekanbaru in period 2017-2022.This research uses desciptive qualitative research type. The research subjects consisted of four successful Firdaus’s team and one community selected by using purposive technique. This studi uses data collection techniques through interviews, observation, and documentation. To achieve the validity of data in this research, the authors use the extension of participation and triangulation.The results showed that the style of political communication Firdaus is verbal communication are that serious, firm, detailed, excessively in communicating and using simple language and educate at the time of campaign and nonverbal communication is that wearing blue malay clothing along with songket and white shirt, friendly to the public, focusing on the audience at the time of the campaign, dialogical campaigns in a room, speaking in a firm and formal tone, preferring direct communication and prioritizes verbal messages. Public relations political strategy in forming a political branding is a media is that social media, face-to-face media, small format media, and outdoor media. The messages of production that arange and make the messages as well as possible and pay attention to the content of any messages that will be delivered both spoken and written. The public that being a target is all of society Pekanbaru City looked by knowledge and attitude sides. Keywords: Political communications style, Public relations political strateg.